Systems analysis and design - Kendall, Kenneth E. (Prentice Hall, 1995)
This text is now available packaged with a HyperCase disk (original, hypertext-based software created by the authors). This innovative software allows students first-hand experience with a business and organizational structure. Students will interview employees, observe office dynamics and practices, analyze prototypes, and review existing systems. All activities are conducted within a business simulation called "Maple Ridge Engineering" and are based on real-life consulting experiences.